2014
DOI: 10.1093/neuonc/nou128
|View full text |Cite
|
Sign up to set email alerts
|

Role of the endothelin axis in astrocyte- and endothelial cell-mediated chemoprotection of cancer cells

Abstract: Bidirectional signaling between astrocytes and cancer cells involves upregulation and activation of the endothelin axis, which protects cancer cells from cytotoxicity induced by chemotherapeutic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 33 publications
0
97
0
Order By: Relevance
“…Besides the intrinsic mechanisms activated in EOC cells, acquisition of chemoresistance could be dependent also by the tumor microenvironment (44). In this regard, recent studies demonstrated that endothelial cells chemoprotect tumor cells through activation of ET-1 axis (45). Therefore, we can hypothesize that other mechanisms activated by ET B R, heterogeneously expressed on tumor cells as well as on endothelial cells, might also contribute to sensitize tumor cells to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the intrinsic mechanisms activated in EOC cells, acquisition of chemoresistance could be dependent also by the tumor microenvironment (44). In this regard, recent studies demonstrated that endothelial cells chemoprotect tumor cells through activation of ET-1 axis (45). Therefore, we can hypothesize that other mechanisms activated by ET B R, heterogeneously expressed on tumor cells as well as on endothelial cells, might also contribute to sensitize tumor cells to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes were previously shown to protect melanoma cells from chemotherapy via the endothelin-endothelin receptor signaling axis (38)(39)(40), and by direct contact through establishment of functional gap junctions via connexin 43 (41,42). However, the role of astrocytes in facilitating the primary growth of brain-metastasizing melanoma cells is unknown.…”
Section: Astrocytes Facilitate the Initial Growth Of Metastatic Melanmentioning
confidence: 99%
“…Important evidences recently defined a key role of ET-1 axis in drug resistance. In a model of brain metastasis from breast cancer, it has been demonstrated that bidirectional signaling between astrocytes and tumor cells involves upregulation and activation of ET-1 axis, which protects tumor cells from cytotoxicity induced by chemotherapeutic drugs such as taxol (15,24). Moreover, macitentan abolishes astrocyte-and endothelial cell-mediated chemoprotection (15).…”
Section: Role Of Et-1 In the Interactions Of Tumor Cells With The Micmentioning
confidence: 99%